Fish diversity of the Bengawan Solo River estuary, East Java, Indonesia - VERYL HASAN; NANTASA E. ANDRAINI; WAHYU ISRONI; LUTHFIANA A. SARI; AYU L. NAFISYAH; NINA N. DEWI; DIAN N. A. PUTRI; TYAS A. B. PRASASTI; ACHMADI A. RAMADHANIa; KIKI DANIEL; JOSIE SOUTH; LUCAS O. VIEIRA; FELIPE P. OTTONI; MAFTUCH MAFTUCH; ABDUL R. FAQIH; PANDU. Y. A. P. WIRABUANA; MUHAMMAD B. TAMAM; FITRI S. VALEN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hasan V, Andraini NE, Isroni W, Sari LA, Nafisyah AL, Dewi NN, Putri DNA, Prasasti TAB, Ramadhani AA, Daniel K, South J, Vieira LO, Ottoni FP, Maftuch, Faqih AR, Wirabuana PYAP, Tamam MB, Valen FS. 2023. Fish diversity of the Bengawan Solo River estuary, East Java, Indonesia. Biodiversitas 24: 2207-2216. Bengawan Solo River is the longest river in Java which flows from Mount Lawu and empties into the North Coast of Java. The watershed is a hot spot for fish species diversity, especially in the estuary area. The purpose of this study was to initiate an inventory of fish species, their abundance, and biodiversity assessment based on the Shannon diversity index (H'), evenness index (E), and dominance index (C) in the Bengawan Solo River estuary. The research was conducted from September to November 2022 at three stations with different ecological types and environmental conditions. Fish sampling was carried out using a gill net attached to a boat. In this study, 44 fish species from 22 families were identified. The highest abundance of fish was obtained from the Ariidae family, namely the Spotted sea catfish Arius maculatus (Thunberg, 1792) and Sagor catfish Hexanematichthys sagor (Hamilton, 1822). The fish diversity index obtained was 1.2-3.01, the uniformity index obtained was 0.7-0.92, and the dominance index obtained was 0.07-0.33. The H', E, and C at Station 2 have higher values ??than the other stations. The diversity expressed in H' values ??at the three research stations indicates that the mangrove in the Bengawan Solo River estuary area has a high diversity of fish species.